Morphological examination is more effective than cell viability assays in the characterization of myotube atrophy - Akpulat, Ugur (Annals of Medical Research, 2023)
Aim: Skeletal muscle atrophy is a significant health problem associated particularly with aging, cancer, and metabolic diseases, leading to a decline in quality of life and responses to treatment. During skeletal muscle atrophy, the balance between protein synthesis and degradation in the tissue is disrupted in favor of protein degradation. This condition results in a reduction in muscle mass and loss of strength and function in the muscles. In order to elucidate the molecular mechanisms causing skeletal muscle atrophy, prevent the processes leading to atrophy, and test the effectiveness of emerging therapeutics, in vitro models that mimic atrophic conditions are commonly used. In these models, typically utilizing primary myoblasts obtained from tissues or myoblast cell lines, either cell viability assays or myotube morphology analyses are employed to determine the degree of atrophy occurring during differentiation. In this study, the two different approaches, which are generally used interchangeably, have been mutually evaluated for their ability to characterize the features of myotube atrophy.Materials and Methods: The myotube atrophy model was established by subjecting differentiating C2C12 cells from myoblasts to myotubes to varying doses of a synthetic glucocorticoid, dexamethasone. Atrophic changes occurring dose-dependently in myotubes were evaluated using the commonly employed MTT cell viability assay and myotube diameter measurement analysis.Results: While myotube diameter measurement can grade the extent of atrophy in myotubes, the MTT assay, although unable to directly assess the degree of myotube atrophy, demonstrated that the decrease in cell viability indicates the cause of myoblast atrophy.Conclusion: While cell viability tests and myotube morphology analyses are commonly used interchangeably to assess myotube atrophy, these two approaches can characterize different aspects of myotube atrophy. The choice of approach should be determined based on the research nature, considering their abilities to characterize myotube atrophy.
Keywords: Skeletal muscle atrophy; Myotube atrophy; MTT assay; Myotube morphology